Exploring Guided Inquiry Learning with PhET Simulation to Train Junior High School Students Think Critically - Erni Yulianti; Nailah Nur Zhafirah; Nurul Hidayat (Universitas Lambung Mangkurat, 2021)
Until recently, not only students in middle high schools but also in a university have difficulties in understanding either mathematical representations or physical concept behind scientific phenomena. Those difficulties are then associated with a low level of critical thinking. For instance, in physics, it seems to be not easy for students to attain proper relation among wave speed, wavelength, and frequency. This unproper understanding contributes to students’ low critical thinking skill. One of the most effective ways to overcome the problem is to use student-centred learning with interactive, animated, and game-like learning experiences. Guided inquiry learning and a freely App “Physics Education Technology (PhET)” are believed to meet the criteria. This study focused on the students’ knowledge construction process to be able to think critically the wave-related concepts. This PhET-assisted guided inquiry learning strategy was addressed to 25 students at a junior high school in Indonesia. The objective is to explore the stages of inquiry learning approach using PhET, especially on training them to attain their critical thinking skill. This is a qualitative study that purely involves in-class observation. The lesson plan and student worksheets were prepared as the research instruments. As the results, we found that the use of PhET in the guided inquiry learning model can help students acquire to learn the concept of wave speed, wavelength, and frequency with critical thinking.